PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN - Tri Wulan Sundari; Wiwik Utami (Universitas Mercu Buana, 2013)
Abstract: This study aims to determine the effect on the value of the company's financial performance with the dividend policy as a moderating variable. The population in this study are all banking companies listed on the BEI. Sampling method performed with saturated sampling method, and based on predetermined criteria, the number of samples is a sample of 15 banking companies that pay dividend during the period 2007-2012.The research data is secondary data obtained from the Indonesian stock exchange (www.idx.co.id) and ICMD 2007-2012. The results showed that: 1) capital are significant positive influence to the firm value, 2) dividend policy are able to significantly moderate influence to the capital on the value company, 3) asset quality are not significant positive influence to firm value, 4) dividend policy are not able to significantly moderate influence to the asset quality on the value company, 5) earningare not significant positive influence to the firm value, 6) dividend policy are able to significantly moderate influence to the earning on the value company, but with negative effect, 7) liquidity are significant negative influence to the firm value, 8) dividend policy are able to significantly moderate influence to the liquidity on the value company.Keywords: financial performance, firm value, dividend policy